2017
DOI: 10.1111/asj.12829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taurine on plasma glucose concentration and active glucose transport in the small intestine

Abstract: Taurine lowers blood glucose levels and improves hyperglycemia. However, its effects on glucose transport in the small intestine have not been investigated. Here, we elucidated the effect of taurine on glucose absorption in the small intestine. In the oral glucose tolerance test, addition of 10 mmol/L taurine suppressed the increase in hepatic portal glucose concentrations. To investigate whether the suppressive effect of taurine occurs via down-regulation of active glucose transport in the small intestine, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Researchers had demonstrated that gut microbiota could generate short-chain fatty acid, including acetic acid, propionic acid, and regulate the host blood glucose in turn [31]. And the change of taurine and hypotaurine were also in accordance with the fact that taurine could downregulate the maternal blood glucose concentrations [32].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Researchers had demonstrated that gut microbiota could generate short-chain fatty acid, including acetic acid, propionic acid, and regulate the host blood glucose in turn [31]. And the change of taurine and hypotaurine were also in accordance with the fact that taurine could downregulate the maternal blood glucose concentrations [32].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…These metabolites are antioxidant and anti-inflammatory agents. 33 The main natural dietary sources are foods of animal origin, particularly seafood. 34 Regarding its effect on glucose metabolism, taurine and hypotaurine have been shown to lower blood glucose levels and improve hyperglycemia and hyperglycemia-induced insulin resistance in mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, taurine and hypotaurine increased their abundance in plasma after the LSI. These metabolites are antioxidant and anti-inflammatory agents 33. The main natural dietary sources are foods of animal origin, particularly seafood 34.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in gastric inhibitory polypeptide, glucagon-like peptide-1 and ghrelin (incretin hormones (i.e., gut hormones that are secreted after ingestion)) in a high-protein diet improve insulin sensitivity and beta cell function [ 26 ]. After a lifestyle intervention, there was an increased plasma abundance of taurine and hypotaurine, which are anti-inflammatory and antioxidant metabolites [ 27 ], and there was reduced glucose concentrations to reflect improvements in hyperglycemia and insulin resistance [ 28 ]. Alterations in N-acetyl-D-galactosamine, putrescine and 7-methylguanine were linked to regression to normoglycemia, which was independent of the baseline HbA1c and weight loss [ 4 ].…”
Section: Diabetes Cardiovascular Disease and Metabolitesmentioning
confidence: 99%